Reading strategies in French written comprehension among DLP and non DLP learners in Kelantan - Mahmad Kamel, Nurul Amalina; Abdul Halim, Hazlina; Abdul Jabar, Mohd Azidan (Human Resource Management Academic Research Society, 2023)
The Kementerian Pendidikan Malaysia has unveiled a program called the Dwi-Language Program. This Dwi-Language Program, or DLP, is implemented in a few schools. Science and Mathematics are the only disciplines taught in English. According to the DLP, the outcomes of the French learners have improved for reading comprehension. This mixed-methods study's purpose was to highlight reading comprehension techniques, particularly the use of PROB, or Problem-Solving Strategies, among DLP and non-DLP students in Kelantan. The respondents in this survey are third-language learners of French. They were in DELF level A1 and ranged in age from 14 to 17. Rafi's Survey of Reading Strategies (SORS) (2002) surveys were taken into consideration for this study. This survey will be administered at a few Kelantan schools. 84 respondents from the DLP class and 68 respondents from the non-DLP class made up the sample for this study. They will get a questionnaire made up of 30 questions separated into three categories: Global strategies (GLOB) (13 items), Support strategies (SUP) (9 items), and Problem-Solving strategies (PROB) (8 items).